The Malaysia Ppoperty Market: A Viewpoint - Abdul Rahman, Rosdi (Fakulti Ukur dan Harta Tanah, 1991)
Microsoft Word - 12-01-2008 01;25;52PM THE MALAYSIAN PROPERTY MARKET: A VIEWPOINT by Rosdi Ab Rahman Jabatan Pengurusan Hartabenda dan Penilaian Fakulti Ukur Universiti Teknologi Malaysia l.O Introduction The property market in Malaysia, as with other countries are cyclical in nature. They are positively correlated with the movements and the performance of the economy. Over the past thirty years, the Malaysian property market has endured three market cycles, and now we are on the upswing of the cycle. The first "boom" between 1963 and 1964 was mainly the result of a high output and value of primary commodities in the international market. Price stabilized in the ensuing years until 1969 when political chaos resulted in an uncertain economy until 1971. The promulgation of the Second Malaysia Plan in 1971, triggers the recovery of the economy and we experience the second "boom". Rapid expansion of the public sector, finance and business sectors occurred, fuelled by strong commodity prices, mass rural-urban migration and the increasing purchasing power of an expanding middle class. It is also important to note that during this period (1971-1973) the government introduced the principle of 'property owning democracy'. This, coupled with the introduction of subsidized housing loans to civil servants, revived the confidence of property developers and owners throughout the country who then embarked on massive housing developments. The continuous growth in the property market from 1973 onwards was checked by a short spell of recession in 1974 due to the global spiralling of oil prices. Thereafter property prices continued on an upward trend attributed by Increased cost of labour and building materials. This leads to the third boom in the period of 1980 and 1983. Paper presented during the Seminar in conjuction with A Study Visit From Hong Kong Polytechnic, at the Faculty of Built Environment, UTM, Skudai, January 14th 1991.